Characteristics Of HIV-Infected Tuberculosis Patients In Kota Bharu Hospital, Kelantan From 1998 To 2001. - Mohammad, Zahiruddin; Naing, Nyi Nyi (2004)
To characterize the demographic profiles, clinical features, radiological patterns and outcomes of treatment of HIV-infected TB patients, a descriptive study was carried out on 149 HIV infected TB cases diagnosed from 1998 through 2001 at Kota Bharu Hospital, Kelantan, Malaysia.